Synthesis and Evaluation of Translocator 18 kDa Protein (TSPO) Positron Emission Tomography (PET) Radioligands with Low Binding Sensitivity to Human Single Nucleotide Polymorphism rs6971 - Zanotti-Fregonara, Paolo (American Chemical Society, 2014)
[Image: see text] The imaging of translocator 18 kDa protein (TSPO) in living human brain with radioligands by positron emission tomography (PET) has become an important means for the study of neuroinflammatory conditions occurring in several neuropsychiatric disorders. The widely used prototypical PET radioligand [(11)C](R)-PK 11195 ([(11)C](R)-1; [N-methyl-(11)C](R)-N-sec-butyl-1-(2-chlorophenyl)-N-methylisoquinoline-3-carboxamide) gives a low PET signal and is difficult to quantify, whereas later generation radioligands have binding sensitivity to a human single nucleotide polymorphism (SNP) rs6971, which imposes limitations on their utility for comparative quantitative PET studies of normal and diseased subjects. Recently, azaisosteres of 1 have been developed with improved drug-like properties, including enhanced TSPO affinity accompanied by moderated lipophilicity. Here we selected three of these new ligands (7–9) for labeling with carbon-11 and for evaluation in monkey as candidate PET radioligands for imaging brain TSPO. Each radioligand was readily prepared by (11)C-methylation of an N-desmethyl precursor and was found to give a high proportion of TSPO-specific binding in monkey brain. One of these radioligands, [(11)C]7, the direct 4-azaisostere of 1, presents many radioligand properties that are superior to those reported for [(11)C]1, including higher affinity, lower lipophilicity, and stable quantifiable PET signal. Importantly, 7 was also found to show very low sensitivity to the human SNP rs6971 in vitro. Therefore, [(11)C]7 now warrants evaluation in human subjects with PET to assess its utility for imaging TSPO in human brain, irrespective of subject genotype.